PERFORMANCE AND HETEROTIC ESTIMATION OF GROWTH IN INTRASPECIFIC CROSSING OF GIANT GOURAMY - Didik Ariyanto; Nunuk Listiyowati (Indonesian Aquaculture Journal, 2011)
Intraspecific crossing of giant gouramy was done to get better hybrid population. This study was conducted to evaluate the hybrid vigour or heterotic value of the hybrids line, especially for growth rate character. Besides that, we want to know the effect of hybridization on performance of phenotypic variability. Two days post hatching age larvae of four populations i.e. Bastar and Blue-saphire strain, F-1 hybrid and F-1 hybrid reciprocal, were used in this experiment. All fish were reared in aquaria for 30 days period in indoor hatchery. The fish were fed with live food such as Moina and Daphnia for the first ten days, followed by Tubifex for the second ten days and finally, commercial feed were given until the end of the study. The collected data were total length, standard length, and body weight of each population. The results showed that the phenotypic variability of the hybrid population was higher than that of inbred population. Hybrid population from female of Bastar and male of Blue-saphire has better growth than both of its parents. Heterotic values of total length, standard length, and body weight of the hybrid population was 9.5%, 2.9%, and 15.6% respectively. Maternal effect was detected in hybrid population.